2018
DOI: 10.5114/aoms.2016.58744
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C coinfection adversely affects the life expectancy of people living with HIV in northwestern Poland

Abstract: IntroductionHepatitis C (HCV) infection adversely affects survival among people living with HIV, increasing mortality risk due to liver-related causes. In Poland HCV is found among ~30% of HIV infected individuals, with only a small percentage successfully treated for this coinfection. This study aimed to analyze the HCV-associated influence on the life expectancy among HIV/HCV coinfected patients from northwestern Poland.Material and methodsLongitudinal data of 701 (368 HIV monoinfected and 368 HIV/HCV coinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The data on life expectancy of people living with HIV in comparison with clinical characteristics in Polish population are limited, with only reports from Northern part of Poland comparing survival probability among patients with coinfection HIV/HCV [ 21 ]. Only few studies associated survival with HLA-B*5701 variant.…”
Section: Discussionmentioning
confidence: 99%
“…The data on life expectancy of people living with HIV in comparison with clinical characteristics in Polish population are limited, with only reports from Northern part of Poland comparing survival probability among patients with coinfection HIV/HCV [ 21 ]. Only few studies associated survival with HLA-B*5701 variant.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be stressed that G1a, present in 40.2% of the samples and including 46.7% of the AHC cases, has only been identified infrequently in Poland. More particularly, G1a has been reported in only 2.5% of the HCV mono-infections and in 17.8% among the HIV/HCV G1 infected cases 20,44 , and was virtually absent in a former dataset focusing on the global epidemiology of HCV genotype distribution, where only G1b infections were observed in the country. In Poland, G1a cases were previously observed among young individuals, however not linked to IDU transmission, in contrast to what has been reported for other regions.…”
Section: A C C E P T E Dmentioning
confidence: 91%
“…A stable increase in the number of new HIV diagnoses per year is observed across the country, with >22.000 cases diagnosed as of December 2017 19 . In the group of HIV/HCV co-infected patients, a decrease of 17.3 years in life expectancy is reported as well as a low likelihood of survival beyond the age of 65, associated with an increased risk of cardiovascular diseases, diabetes, neurocognitive performance and kidney disease, compared to those that are HCV mono-infected 20 . Although availability of DAA therapies has recently increased, access to treatment is not universal yet and is still prioritized for patients with advanced liver fibrosis, at least in Poland.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…In Poland the percentage of co-infection might reach up to 71% of HIV positive persons and was shown to reduce life expectancy by 17.3 years [19,20]. The HC EP09 and BINECO studies showed that HCV/HIV co-infected patients had HCV RNA found in the semen more frequently than those without HIV infection (37.8% vs. 18.4%) [21].…”
Section: Discussionmentioning
confidence: 99%